PENGARUH PERPUTARAN PIUTANG DAN HUTANG TERHADAP RENTABILITAS EKONOMI PADA KOPERASI UNIT DESA (KUD) MEKAR ABADI DESA TASIK JUANG KECAMATAN LUBUK BATU JAYA - Aris Triyono (LPPM Press STIE Indragiri Rengat, 2018)
This research was conducted at KUD Mekar Abadi Village Tasik Juang, Lubuk Batu Jaya District. The purpose of this study is to determine the effect of accounts receivable and debt turnover on economic profitability at Kekar ​​Mekar Abadi Village Tasik Juang, Lubuk Batu Jaya District. The research was conducted with quantitative methods, namely research describing the effect of accounts receivable and debt turnover on economic profitability at KUD Mekar Abadi Village Tasik Juang, Lubuk Batu Jaya District. By analyzing the data using multiple regression, correlation coefficients, and hypothesis testing which will later be assisted by using SPSS version 21. From the results of this study shows that the accounts receivable turnover has a significant effect on economic profitability, and debt diesn’t have a significant effect on economic profitability.